Eksplorasi Etnomatematika pada Makanan Ringan Tradisional (Jipang) dan Kaitannya dengan Pembelajaran Matematika - Amran, Nurul Khofifah; Nur, Fitriani; Mattoliang, Lisnasari Andi (Supermat : Jurnal Pendidikan Matematika, 2024)
This study examines ethnomathematics in traditional jipang food, which relates mathematical concepts to cultural aspects, this has the potential to increase student interest through contextual learning. In addition, this study fills the study in the Bugis tribe area and integrates cultural values ​​​​in education, thus enriching the learning experience. This study aims to determine the process of ethnomathematics exploration in traditional snacks (Jipang) and its relationship to mathematics learning and its cultural values. Ethnomathematics examines the application of mathematical reasoning in everyday culture, especially in making traditional snacks such as Jipang. The method used is qualitative research with an ethnographic approach, which includes observation, interviews, and documentation. The study was conducted in the Wajo Regency, especially among the Bugis tribe. The results of this study indicate that traditional Jipang snacks contain mathematical concepts, namely cuboid geometry, cubes, rectangles, and squares, related to mathematics learning, namely the concept of flat shapes and spatial shapes in elementary schools. These snacks reflect a philosophy of life that prioritizes the importance of the main ingredients and the way they are made, which involves family cooperation. This research is also expected to provide new insights into contextual and relevant mathematics teaching, improve students' understanding of mathematical concepts, and enrich the learning experience by integrating local culture. Showing the importance of utilizing traditional food as an effective learning tool in mathematics education.